Downregulation of cystathionine γ lyase and endothelial nitric oxide synthase and reduced responsiveness of α1A adrenergic receptors in the kidneys of left ventricular hypertrophied Wistar Kyoto rats - Ahmad, A.; Sattar, M.A.; Rathore, H.A.; Khan, S.A.; Abdullah, N.A.; Johns, E.J. (Scientific and Technical Research Council of Turkey, 2016)
This article explores the relationship between the renal expression of cystathionine gamma lyase (CSE) and endothelial nitric oxide synthase (eNOS) and the responsiveness of α1A adrenergic receptors in the renal vasculature following left ventricular hypertrophy (LVH) in rats. LVH was established by administering isoprenaline (5 mg/kg, 5 injections subcutaneously, 72 h apart) with 62 mg/L caffeine in drinking water for 2 weeks. Renal vasoconstrictor responses were measured using local administration of adrenergic agonists noradrenaline (NA), phenylephrine (PE), and methoxamine (ME) and the selective α1A adrenergic antagonist 5-methylurapidil (5- MeU). Mean arterial blood pressure was higher (144 ± 9 vs. 116 ± 4 mmHg) and renal cortical blood perfusion was lower in the LVH group (102 ± 5 vs. 157 ± 19 bpu) compared to the control group (P < 0.05). There was a 68% downregulation of mRNA for renal CSE and 79% for eNOS in the LVH group compared to the control group (taken as 100%) (P < 0.05). The high dose of 5-MeU attenuated the vasoconstrictor responses to NA by 33%, PE by 44%, and ME by 43% in the LVH group compared to the same dose in the control group. The reductions in basal renal cortical perfusion and α1A adrenergic receptor vasoconstrictor responses in LVH were associated with the downregulation of the CSE/H2S and eNOS/NO pathways.